2021
DOI: 10.35848/1882-0786/abdac3
|View full text |Cite
|
Sign up to set email alerts
|

Increase in the infield critical current density of MgB2 thin films by high-temperature post-annealing

Abstract: We propose a novel fabrication technique based on the formation of a Nb protective layer on a MgB2 thin film and high-temperature post-annealing to increase the critical current density (J c) of MgB2 films under an external magnetic field. Analyses of the crystal structure and the composition of the processed MgB2 films confirmed the suppression of the evaporation and oxidation of Mg by high-temperature annealing above 550 °C. The MgB2 film annealed at 650 °C exhibited a J c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 15 publications
0
12
3
Order By: Relevance
“…This suggests that the Nb protective layer was slightly oxidized during the annealing process. MgB 2 (002) peaks were not observed for any of the samples, in contrast to our previous study, 17) in which MgB 2 (002) peaks were observed in the XRD patterns of Nb/MgB 2 /B/Si samples. This could be because the Nb protective layer in this study was thicker than that in the previous study 17) (6 versus 3 μm).…”
contrasting
confidence: 99%
See 4 more Smart Citations
“…This suggests that the Nb protective layer was slightly oxidized during the annealing process. MgB 2 (002) peaks were not observed for any of the samples, in contrast to our previous study, 17) in which MgB 2 (002) peaks were observed in the XRD patterns of Nb/MgB 2 /B/Si samples. This could be because the Nb protective layer in this study was thicker than that in the previous study 17) (6 versus 3 μm).…”
contrasting
confidence: 99%
“…MgB 2 (002) peaks were not observed for any of the samples, in contrast to our previous study, 17) in which MgB 2 (002) peaks were observed in the XRD patterns of Nb/MgB 2 /B/Si samples. This could be because the Nb protective layer in this study was thicker than that in the previous study 17) (6 versus 3 μm). Nb (110) peaks can be observed in all the samples whereas the small peaks of NbO (111) were seen only in the samples annealed for 3 h and 5 h. The presence of sufficient metal Nb and significantly small generation of NbO and Nb 2 O 5 phases after the annealing indicates that Nb layers blocked the oxygen diffusion from the atmosphere to the MgB 2 layer during the post-annealing.…”
contrasting
confidence: 99%
See 3 more Smart Citations